Review of mix-and-match approach and binocular intraocular lens systems - Naujokaitis, Tadas; Łabuz, Grzegorz; Khoramnia, Ramin; Auffarth, Gerd U. (Journal of Clinical Medicine, 2025)
In the mix-and-match approach and in binocular intraocular lens (IOL) systems, two different IOL models are implanted in each eye to achieve the desired binocular outcome. In the mix-and-match approach, the surgeon selects the IOL models to be combined according to the clinical situation, the patient’s needs, and personal preference. Combinations described in the literature include, among others, two bifocal IOLs, an extended-depth-of-focus (EDoF) IOL with a bifocal lens, a trifocal lens with an EDoF IOL or an enhanced monofocal IOL, and two EDoF models utilizing different optical principles. The outcomes depend on the selected combination of IOL models. Binocular IOL systems consist of a fixed combination of two lenses, developed to be complementary in binocular vision. Initial data indicate that they can achieve a depth of focus similar to that with a bilateral implantation of a trifocal IOL. However, comparative studies are needed to evaluate if the postoperative binocular outcome differs from that achieved with the conventional approach. The mix-and-match implantation and binocular IOL systems expand the options available to tailor the IOL selection to the patient’s needs.
Gesehen am 03.11.2025